NEW STEP IN THE LIFE QUALITY IMPROVEMENT OF PATIENTS WITH MUCOVISCIDOSIS: TOBRAMYCIN FOR ANAPNOTHERAPY - V. V. Chernikov; S. A. Krasovskiy (Union of pediatricians of Russia, 2012)
This article is dedicated to a monogenic polysystemic disease - mucoviscidosis; its course severity and prognosis are to a large extend determined by the degree of lung affection, infection and chronic inflammatory process development in the airways. The authors show the derangement of the quality of life in children with mucoviscidosis and examine approaches to the therapy adherence issues, which is important for the treatment effectiveness. On the example of their own study and international experience they show the effectiveness of the inhalation technique of the drug delivery to a pathological nidus.